Transforming School Culture in Strengthening Teacher Capacity: Lessons from the Implementation of PSP - Hasan, Kamaruddin; Krismanto, Wawan; Zainal, Zaid (Seminar Nasional LP2M UNM, 2025)
Abstract. This study aims to explore the forms of school culture transformation in strengthening teacher capacity in schools participating in the Program Sekolah Penggerak (PSP). The focus of the research is directed at understanding how principals and teachers interpret their involvement in the PSP and how changes in their beliefs, attitudes, and behavior reflect shifts in the school's organizational culture. A qualitative approach, employing descriptive methods, was used in this study. Data were collected through observation, in-depth interviews, and focus group discussions (FGDs) with three principals and twelve teachers from six schools in Barru Regency, South Sulawesi. The results show that the PSP has encouraged the birth of four main cultural transformations in schools, namely: (1) the growth of a renewed enthusiasm for learning among principals and teachers, (2) the reorientation of teacher learning goals from an administrative orientation to an orientation towards change, (3) a new focus on improving the quality of student learning, and (4) the development of a sense of community through teacher learning communities. These four transformations form a new school culture pattern characterized by being reflective, collaborative, and oriented towards sustainable change. The PSP has been proven not only to increase the individual capacity of teachers and principals, but also to foster a collective learning culture that serves as a foundation for sustainable educational transformation in schools. Keywords: PSP; school culture; teacher capacity